Annealing effect for self-assembled monolayers formed from terphenylethanethiol on Au(111) - Azzam, Waleed; Al-Rashdi, Awad; Subaihi, Abdu; Rohwerder, Michael; Zharnikov, Michael; Bashir, Asif (Physical chemistry, chemical physics, 2020)
The structure and morphology of self-assembled monolayers (SAMs) prepared on Au(111) from solutions of terphenylethanethiol (TP2) at room temperature and subsequently annealed at temperatures up to 473 K were investigated using scanning tunneling microscopy. This system is of particular interest because of its metastable character, holding potential for its tailored modification. Indeed, the data suggest the formation of several different structural phases,viz.alpha, beta, gamma, and delta, appearing progressively for the as-prepared and annealed samples. The consecutive alpha -> beta -> gamma -> delta phase transitions occurring with increasing annealing temperature involved a continuous reduction of the molecular packing density and significant changes in the substrate morphology. The major morphological changes were the appearance and progressive growth of monoatomic gold islands, on top of which the TP2 phases were formed, representing in all cases a single domain for a particular island and restricted only by the island size. For all the phases, inclined molecular orientation was assumed while a so-called lying-down arrangement, in which the TP2 backbones are orientated parallel to the gold surface, was not observed. A nearly complete desorption of the TP2 molecules was recorded at an annealing temperature of 473 K, accompanied by the drastic change in the surface morphology.
Gesehen am 08.06.2021